ANALISIS STRATEGI BAURAN PEMASARAN DALAM MENDUKUNG PENGEMBANGAN USAHA HSL STORE KENDARI - Makmur Kambolong; Munawir Makmur; Candra Puspita Ningtyas; Malika (Halu Oleo University, 2024)
This study analyses the Marketing Mix Strategy to Support the HSL Store Kendari Business Development. The method used in this study is qualitative research with a case study method. In this study, the analysis method applied is SWOT. SWOT is a tool used to formulate company strategy factors. The study results show that HSL Store Kendari applies a marketing mix with a focus on quality products, competitive prices, digital promotions through Instagram, and a strategic location near campus even though access is less than optimal. Skilled employees, standardized production processes, and a comfortable store environment are the main priorities in maintaining customer satisfaction. Based on the SWOT analysis which shows a position in quadrant I, HSL Store utilizes internal strengths to capture external opportunities with strategies such as collaborating with campuses and schools, increasing digital marketing to expand market reach, and ensuring the availability of quality raw materials. This strategy is expected to increase revenue and customer loyalty, especially during the graduation season.